Functor of semiadditive functionals - Djabbarov, G. F.; Davletov, D. E. (Methods of Functional Analysis and Topology, 2008)
In the present paper we describe semiadditive functionals and establish that the construction generated by semiadditive functionals forms a covariant functor. We show that the functor of semiadditive functionals is a normal functor acting in category of compact sets.